Eosinophilic appendicitis caused by schistosoma japonicum: A case report and review of the literature - Wasana Kanoksil (2018)
Parasitic appendicitis is uncommon. The authors reviewed the pathology of 4,130 appendices resected over the past 10 years (2000 to 2009). Only one case of eosinophilic appendicitis caused by Schistosoma japonicum was identified. The overall prevalence of schistosomal appendicitis was 0.024%. The case was a 61-year-old woman who presented with right lower quadrant abdominal pain. She had been a farmer in Chumphon and Surat Thani Provinces, which are endemic for schistosomiasis in Thailand. Physical, laboratory and ultrasound examinations were suggestive of acute appendicitis. She underwent emergency appendectomy. Intraoperative findings revealed a ruptured appendix with a fecalith in the appendiceal lumen. The histopathologic diagnosis was suppurative eosinophilic appendicitis with schistosomal ova in the mucosa, submucosa, muscular layer and vascular lumens, identified as S. japonicum eggs. The patient was treated for the parasite with praziquantal. We briefly review the clinicopathologic features and pathogenesis of schistosomal appendicitis.